Detection of trace amounts of target DNA from massive background of nucleic acids by using the LM‐PCR‐based preamplification method. (29th August 2017) - Pan, Xiaoming; Wang, Jing; Zhang, Yanfang; Dong, Ping; Li, Chunchuan; Liang, Xingguo
Abstract: The sensitivity and specificity of DNA detection may decrease when the target DNA is in very low abundance. To effectively detect trace amounts of target DNA from massive background of nucleic acids, we have developed a powerful multiplex preamplification method based on ligation‐mediated PCR that can greatly enrich multiple target DNAs from massive backgrounds. By employing type IIS restriction endonuclease (REase) and specifically designed oligonucleotide adapters, target DNA can be preamplified with high efficiency and sensitivity. Combining with normal PCR, 10 copies of target DNA was effectively detected from over 10 8 times more excessive backgrounds with high specificity and 10 times more effectively than conventional PCR. In particular, the usage of universal primer in the preamplification PCR (pre‐amp PCR) ensured that multiple targets could be equivalently amplified, which was confirmed by quantitative PCR (qPCR), indicating it could meet the demands of high‐throughput detection. The flexibility and applicability of pre‐amp PCR was validated by using different microorganisms DNA as targets and employing two different type IIS REases. The results suggest that the pre‐amp PCR method has broad application prospects in various gene detection fields.